(untitled) (The Research of Medical Science Review, 2025)
Background: Acute myocardial infarction stands as a worldwide major medical threat which specifically leads to high mortality rates among people with renal impairment. Chronic kidney disease (CKD) along with acute kidney injury (AKI) creates additional heart disease risks because of problems with endothelial functioning and inflammatory responses and disrupted electrolyte control. The clinical outcomes of patients with renal dysfunction worsen after an AMI because their medical intervention is delayed and their bleeding susceptibility increases in tandem with their inefficient medication breakdown mechanisms. Knowledge about how renal dysfunction affects hospital death rates enables the creation of improved treatment methods which enhance patient recovery. Objectives: to examines the effect of kidney function deterioration on hospital fatality rates of AMI patients while analyzing population-specific clinical features and essential predictors of outcome. Study design: A Retrospective Cohort Study. Place and duration of study. From 15 September 2024 to 14 March 2025 Cardiology Department Bolan Medical Complex Hospital Quetta/ Sandeman Provincial Hospital, Quetta Methods: The study analyzed patients who suffered heart attack while treating them at a tertiary care healthcare center. The research analyzed patients according to their renal function status through the eGFR measurement where values below 60 mL/min/1.73m² were identified as impaired. An analysis took place for demographic along with clinical information. The researchers evaluated hospital-based mortality rates as their main study outcome. The researchers analyzed continuous variables by reporting their mean values with standard deviation (SD) and using the t-test for comparisons while categorical variables received chi-square test analysis. The researchers considered statistical significance at a p-value level lower than 0.05. Results: 50 patients composed the study sample. The study mentioned that patients displayed an average age of 65.4 ± 10.7 years yet this measure exhibited a substantial difference between patients with renal dysfunction who had an average age of 68.2 ± 9.8 years and those who had normal renal function with an average age of 61.9 ± 10.2 years (p = 0.02). Hospital survivors among patients with normal renal function reached 9.3% while those in the renal dysfunction group experienced higher hospital mortality at 25.6% (p = 0.004). Patients who suffered from renal impairment showed more frequent occurrences of cardiogenic shock as well as major bleeding when compared to other patients (p = 0.01 and p = 0.03, respectively). Hospital stays for patients with renal dysfunction reached 8.7 ± 3.4 days while patients with normal renal function stayed 6.2 ± 2.8 days (p = 0.01). Conclusion: The condition of patient kidneys stands as a major risk factor which affects hospital death rates in AMI patients. Patients under these conditions face an elevated threat of pathologic events that involve cardiogenic shock as well as bleeding complications. In order to enhance survival rates early risk determination and personalized treatment approaches must be employed. Multidisciplinary intervention remains essential to create optimized care which minimizes mortality rates within this particular population.